Application of Continuous Passive Motion (CPM) in elbow rehabilitation: a literature survey - Aline Marian Callegaro; Marisa Pereira Gonçalves; Alexandre Dias da Silva; Inácio da Fontoura Limberger (O Mundo da Saúde)
Continuous Passive Motion (CPM) is used in post-trauma or articulations surgery rehabilitation to articulate, and its application may produce positive results in members` rehabilitation. This study aimed to analyze and to discuss the use of CPM equipment in elbow rehabilitation through a bibliographical survey of studies published in the last 10 years. This bibliographical survey was done in a computerized databank of Virtual Library in Health, EBSCO HOST, PeDRO, Cochrane Library and Science Direct. For locating studies, we used the keywords continuous passive movement, elbow and elbow MPC/CPM in English, Portuguese and Spanish. Complete articles in Portuguese, English and Spanish were selected. The research strategy focused on studies of the treatment of elbow pathologies using CPM as an isolated method and associated to other physiotherapeutic techniques. The sample was composed by 16 newspaper articles. In 11 articles, CPM application associated or not to other physiotherapeutic methods, has produced beneficial results; 1 did not present differences in the comparison between the use of (CPM) and the use of other techniques; 2 presented positive results, emphasizing specific cares, and 2 called for more studies for result verification. Therefore, it was possible to shoe that researchs are now exploring the use of CPM in elbow rehabilitation, but parameters used and application methods are not well explained. In addition, it was possible to perceive that today CPM is used as an adjuvant method of physiotherapeutic rehabilitation, with the prevalence of positive results: